If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3y = 6forx Solving 2x + -3y = 6forx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6forx' to each side of the equation. 2x + -6forx + -3y = 6forx + -6forx Reorder the terms: -6forx + 2x + -3y = 6forx + -6forx Combine like terms: 6forx + -6forx = 0 -6forx + 2x + -3y = 0 Add '3y' to each side of the equation. -6forx + 2x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 -6forx + 2x + 0 = 0 + 3y -6forx + 2x = 0 + 3y Remove the zero: -6forx + 2x = 3y Combine like terms: 3y + -3y = 0 -6forx + 2x + -3y = 0 The solution to this equation could not be determined.
| 3/4y=4/7 | | a=k*x | | (a-4)(3a+2)(a+4)= | | h=1+20t-5t^2 | | 5(6ax+y)=29ax-6y | | 3y+5/7 | | 8x+30=10x+2 | | x^2+4s-45=0 | | 6x=10x-2 | | x+(x+10)+(x-40)=180 | | 42x-7= | | -1x^2/-10+9x/10+11/5 | | 0=-1x^2/10+9x/10+11/5 | | -0.1x^2+0.9x+2.2=0 | | 5p-13=8 | | a+2d=18 | | 3/20*2/3+3/20*1/3 | | (12x-17y)= | | 2x^2+x+5=11 | | 6x+36=10x-12 | | 3(9*9)-18(9)-81=0 | | 3(-3*-3)-18(-3)-81=0 | | 3(-3*-3)-18x-81=0 | | 3(x+y)=8y-7 | | 3(4y+3)=30 | | 6x+14=-14-8 | | 36=2l+2(6) | | 34=2l+2(4) | | 42=2l+2(6) | | 5-21nx=6 | | 34=2l+2(2) | | 24x^6y^2/6x^2y |